Confidentiality, Privacy, and Respect: Experiences of Female Sex Workers Participating in HIV Research in Andhra Pradesh, India. (February 2014) - Reed, Elizabeth; Khoshnood, Kaveh; Blankenship, Kim M.; Fisher, Celia B.
Female sex workers (FSWs) from Andhra Pradesh, India, who had participated in HIV research were interviewed to examine participant perspectives on research ethics. Content analysis indicated that aspects of the consent process, staff gender and demeanor, study environment, survey content, time requirements for study participation, and perceived FSW community support for research were key factors influencing whether FSWs perceived their confidentiality and privacy had been maintained, and whether they felt the study was conducted respectfully. Findings suggest that partnership with community-based organizations and investigation of participant's experiences in HIV prevention research can provide critical information to best inform research ethics protocols, a particular priority among research studies with highly stigmatized populations, such as FSWs.